Fearless fourteen : a Stephanie Plum novel - Evanovich, Janet (New York : St. Martin's Press, 2008)
Personal vendettas, hidden treasure, and a monkey named Carl will send bounty hunter Stephanie Plum on her most explosive adventure yet.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; Bail bond agents -- New Jersey -- Trenton -- Fiction; Bank robberies -- Fiction; Trenton (N.J.) -- Fiction; Mystery fiction; Humorous fiction